Cerebellar continuous theta-burst stimulation affects motor learning of voluntary arm movements in humans - Li Voti, Pietro; Conte, Antonella; Rocchi, Lorenzo; Bologna, Matteo; Khan, Nashaba; Leodori, Giorgio; Berardelli, Alfredo (The European journal of neuroscience, 2014)
In this study we investigated in healthy subjects whether continuous theta‐burst stimulation (cTBS) over the lateral cerebellum alters motor practice and retention phases during ipsilateral index finger and arm reaching movements. In 12 healthy subjects we delivered cTBS before repeated index finger abductions or arm reaching movements differing in complexity (reaching‐to‐grasp and reaching‐to‐point). We evaluated kinematic variables for index finger and arm reaching movements and changes in primary motor cortex (M1) activity tested with transcranial magnetic stimulation. Peak acceleration increased during motor practice for index finger abductions and reaching‐to‐grasp movements and persisted during motor retention. Peak acceleration decreased during motor practice for reaching‐to‐point movements and the decrease remained during motor retention. Cerebellar cTBS left the changes in peak acceleration during motor practice for index finger abductions and reaching‐to‐grasp arm movements unchanged but reduced peak acceleration at motor retention. Cerebellar cTBS prevented the decrease in peak acceleration for reaching‐to‐point movements during motor practice and at motor retention. Index finger abductions and arm reaching movements increased M1 excitability. Cerebellar cTBS decreased the motor evoked potential (MEP) facilitation induced by index finger movements, but increased the MEP facilitation after reaching‐to‐grasp and reaching‐to‐point movements. Cerebellar stimulation prevents motor retention for index finger abductions, reaching‐to‐grasp and reaching‐to‐point movements and degrades motor practice only for reaching‐to‐point movements. Cerebellar cTBS alters practice‐related changes in M1 excitability depending on how intensely the cerebellum contributes to the task. Changes in M1 excitability reflect mechanisms of homeostatic plasticity elicited by the interaction of an ‘exogenous’ (cTBS‐induced) and an ‘endogenous’ (motor practice‐induced) plasticity‐inducing protocol. We studied whether in healthy subjects cTBS applied over the lateral cerebellum can alter motor practice and retention of ipsilateral index finger and arm reaching movements. Cerebellar cTBS interferes with motor retention. By increasing motor task complexity, cerebellar cTBS interferes also with motor practice. cTBS alters practice‐related synaptic activity in M1, by occluding M1 activity for index finger movements and by inducing homeostatic plasticity mechanisms for arm reaching movements.